Generation 1.5 and Academic Libraries: Strategies for Supporting English Learners (ELs) in Reference and Instruction - Marchese, Megan Margino (Evidence Based Library and Information Practice, 2021)
Background – Compared to native English speakers, English Learners (ELs) often face additional barriers to academic success. Though typically competent in social English, Generation 1.5 ELs struggle with academic English at the postsecondary level and are still considered to be in the process of learning English. As colleges become increasingly linguistically diverse, academic librarians must adapt to support the growing numbers of ELs in the campus community.Objective – This paper aims to provide academic librarians with information on the scope of English Learners in K-12 through postsecondary education, academic challenges of Generation 1.5 students at the postsecondary level, and strategies that librarians can employ to support English learners in the contexts of reference and instruction.Methods – The author searched journals in the disciplines of academic libraries, higher education, Teaching English to Speakers of Other Languages (TESOL), and linguistics. Additional resources searched include education data and statistics, research institute publications, and English as a New Language (ENL) teaching resources. These sources were explored in regard to the topics of EL educational statistics, K-12 ENL programs, ENL pedagogy, ELs in postsecondary education, Generation 1.5 students, ELs’ academic challenges and educational needs, and academic libraries and ELs.Results – A review of the literature on ELs in academic libraries, particularly Generation 1.5 students, reveals that Generation 1.5 is a population that is in need of support at the postsecondary level. Because Generation 1.5 students often hold strong social English skills, they may enter college without an EL designation or specialized academic support. However, research shows that Generation 1.5 students struggle with college-level academic English, specifically in grammar and vocabulary. These challenges impact students’ communicative success both in college classroom and library environments.Conclusion – Academic librarians may adopt pedagogical strategies commonly employed in ENL classrooms to use in reference and instruction environments. Techniques include themes such as awareness of language use and reinforcement of content, and require low-stakes implementation into library practice. Though librarians may be unaware of the language learning needs of their students, such strategies have shown to be useful for all students. Because techniques that are helpful to ELs also typically benefit all students, these strategies are also applicable to native English speakers.